Tutela jurisdicional diferenciada: instrumento para efetividade e celeridade da justiça no Código de Processo Civil e no microssistema coletivo - Sarno, Paulo Alberto (2014)
This study examines the role of differentiated jurisdictional tutelage as an instrument to ensure the effectiveness and the promptness of justice in the Civil Procedure Code and in the collective microsystem. Firstly, some issues involving effective access to justice are approached since they are a fundamental right which seeks to guard the existential minimum embraced by the Constitution. Among the issues investigated it is highlighted the Code of Civil Procedure and the rules involving metaindividual rights, collective tutelage and procedural techniques (cautionary and anticipatory ones as well as supplementary application of the Code of Civil Procedure in collective microsystem). As an example of differentiated tutelage on environmental law, this research addresses the approximation of substantive and procedural rights based on the principles of prevention, precaution and reparation. Specific cases serve as examples of its applicability. This study seeks to demonstrate that access to justice is only for the actual grant of substantive right postulated by the party (Article 5, XXXV, of the Federal Constitution of 1988). For this purpose, legislation must foster procedural mechanisms necessary to materially meet the required pretension, whether injunctive or final. The examination of the procedural syncretism showed that the art.273, paragraph 7, of the Code of Civil Procedure finds natural support on collective microsystem by revealing the symbiosis of procedural techniques, unveiled in the original wording of art.4 of Law 7.347/ 85. Concerning collective demands, the legal microsystem consolidated differentiated jurisdictional protection techniques, which have adapted the procedural instrument to the attainment of the substantive right. The study also addresses the reverse burden of proof (device that favors the achievement of differentiated jurisdictional tutelage), the writ or executive lato sensu nature of consumerist norms and the supplementary application of the Civil Procedure Code. It is also important to stress the collective res judicata and the limitation of cognition in order to demonstrate that the collective microsystem is a model of differentiated jurisdictional tutelage, with a focus on transportation in utilibus, regarding the settlement of res judicata in the class action trial. On another level, the study shows the parity between the art.84 of the Code of Consumer Rights and art.461 of the Civil Procedure Code, for the achievement of specific enforcement or of the equivalent practical result. The study also concludes the unconstitutionality of the art.16 of the Law of Civil Action which is incompatible with the ideals of the effectiveness of jurisdictional tutelage. Therefore, within the collective scope it is designed the effectiveness of the proceedings, with the provision of mechanisms that would support the substantive law on new horizons. Thus, this research reveals how the system of differentiated jurisdictional tutelage, delineated in the Civil Procedure Code and the collective microsystem, is essential for the effectiveness of justice and the achievement of beneficial outcome of the case, expected by society